Governing climate change adaptation in urban Tanzania - Mushi, Lawrencia; Ogweyo, Noel O.; Cosmas, Faraja U. (2026)
Climate change is one of the greatest global health threats of the twenty-first century, with profound implications for health systems and progress toward universal health coverage. In Tanzania, urban areas such as Dar es Salaam are increasingly experiencing climate-related health challenges, including flooding, heat stress, and outbreaks of climate-sensitive diseases such as cholera, malaria, and respiratory infections, placing growing pressure on already constrained urban health systems. Although urban health systems in low- and middle-income countries are increasingly exposed to these risks, evidence on their capacity to govern and implement climate change adaptation actions remains limited. This study aimed to explore the governance capacity of the urban health system for climate change adaptation in Dar es Salaam, Tanzania. An exploratory qualitative study was conducted using in-depth interviews (IDIs) and focus group discussions (FGDs) with key stakeholders involved in health governance, policy development, and health service delivery. A total of 68 participants were purposively selected from municipal health management teams, public health facilities, and academic institutions across four municipal councils in Dar es Salaam. Data were analysed thematically and organised using ATLAS.ti software. The findings revealed strengths and gaps across three key areas of climate change adaptation governance. First, early warning and preparedness mechanisms existed but were constrained by fragmented disease surveillance systems, weak emergency response team functionality, and inadequate climate–health data for decision-making. Second, human resource capacity was supported by available training and research institutions; however, staffing shortages, limited training coverage, and irregular refresher training reduced preparedness for climate-related health emergencies. Third, institutional and material capacity remained inadequate, characterized by limited operational climate change guidelines at the facility level, infrastructure gaps, and insufficient financial and material resources to support effective adaptation. Although municipal health systems in urban Tanzania have initiated climate change adaptation efforts, the governance of these actions remains constrained by uneven and inadequate institutional capacity. Persistent shortages in human resources, infrastructure, and sustainable financing undermine the effectiveness of early warning systems and preparedness mechanisms. Consequently, urban health systems remain insufficiently resilient to complex climate-related health risks. Therefore, strengthening climate-resilient health governance will require targeted investments in workforce capacity, infrastructure, integrated climate-health information systems, sustained financing, and clearer institutional guidelines to support proactive and coordinated adaptation across governance levels.